Hubungan regulasi emosi dengan subjective well being pada remaja dengan orangtua bercerai - Hesti Sri Rahayu (Cognicia, 2020)
Adolescence is a period of tension as individuals begin to recognize the environment and recognize the people in surroundings. Nevertheless in Adolescence on broken home families. Adolescence need emotional regulation to know what they felt, and what they thought and able to evaluate the emotions experienced so as to act rationally not emotionally. So, it is possible if the adolescence with broken home family with high emotional regulation will have a high subjective well being. This study aims to determine the relationship of emotional regulation with subjective well being in teenagers on broken home family. The approach in this research is using a quantitative correlational. Moreover, the number of the subjects in this study were 100 teenagers who had divorced parents in age-range 13-21 years. The purposive sampling technique is used to gain the data. The researcher collect the data using Likert model scale. Then, the researcher used product moment correlation as the data analysis method. The research has uncovered that there is a positive significant relationship between family functioning and psychological well-being in divorced family teenagers, which is shown by probability value 0.000 <0.005